Substitusi Gembili (Dioscorea Esculenta) pada Kue Sagu Keju dalam Peningkatan Pangan Lokal: Analisis Friedman terhadap Uji Hedonik - Muliyana, Yuni; Mahdiyah, Mahdiyah; Dahlia, Mutiara (Sahabat Publikasi, 2023)
This research aims to determine and analyze the effect of the percentage of gembili (Dioscorea esculenta) starch substitution in making sago cheese cake on consumer acceptance through the aspects of color (outside and inside), aroma (butter/cheese and gembili), taste (cheese, gembili and sweet ), and texture (brittle). The research will take place from January 2022 to November 2023 at Jakarta State University. This research is included in quantitative research with experimental methods for 3 treatments (10%, 20% and 30% substitution). Testing with organoleptic tests, namely hedonic tests carried out on 30 somewhat trained panelists. The results of statistical hypothesis testing using the Friedman test show that there is no effect of gembili starch substitution in making sago cheese cake on consumer acceptance in all aspects, so it can be decided that 30% gembili starch substitute for sago cheese cake is the most preferred formula in general and recommended to be developed in further efforts to improve local food that has functional properties.